Enhancing Students’ Reading Comprehension Through Digital Gamification in Junior High School - Abraham, Reyhan Haisung Aulada; Khoiriyah; Sulistyani (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
eading comprehension is a critical skill in English as a Foreign Language (EFL) learning. However, many Indonesian junior high school students face persistent challenges in this area, primarily due to low motivation, lack of engagement, and the continued use of conventional instructional methods. These issues underscore the need for innovative pedagogical strategies that align with learners’ interests and digital habits. This study investigates the effect of digital gamification on students’ reading comprehension using a narrative-based video game titled “I Got This: An Interactive Story” as a digital medium in the learning process. The gamification was implemented without the use of specialized platforms, as game elements were manually integrated by the researcher. A quantitative approach with a quasi-experimental design was employed, involving 60 eighth-grade students at SMPN 1 Tarokan, who were assigned to the experiment group and control group through purposive sampling. The experiment group received instruction through a gamified video game incorporating points, levels, leaderboards, badges, and rewards, while the control group was taught using conventional methods. Both groups completed a pre-test and post-test consisting of 25 multiple-choice questions based on narrative texts. Data were analyzed using the Mann-Whitney U test due to non-normal distribution. The results showed a statistically significant difference between the two groups (p = 0.002), with the experimental group demonstrating greater improvement in reading comprehension. These findings highlight the pedagogical value of narrative-driven digital gamification and offer implications for educators and curriculum designers seeking to modernize reading instruction in alignment with the digital habits of 21st-century learners.